2018
DOI: 10.1155/2018/6920620
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Enhances the Activity of the ACE-2/Ang(1–7)/Mas Receptor Pathway in Lungs of Male Pups from Food-Restricted Mothers and Prevents the Reduction of SP-A

Abstract: In utero growth restriction and being born small for gestational age are risk factors for respiratory morbidity. IUGR (in utero growth retardation) is associated to overall reduction in lung weight, surfactant content and activity, impaired maturation of the alveolar type II cells, and decreased alveolar formation. The renin-angiotensin system (RAS) may be a key target underlying pathophysiological lung alterations. GLP-1 and agonists of its receptor modulate the expression levels of different components of RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 54 publications
3
32
0
Order By: Relevance
“…It has been reported that GLP-1 is closely linked to RAS in multiple organs (Zhang et al, 2015;Fandiño et al, 2018). Therefore, we investigated the liraglutide-mediated regulation of RAS system to identify the role of the RAS in NAFLD progression and improvement.…”
Section: Liraglutide Regulates Ras Component Expression In the Liversmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that GLP-1 is closely linked to RAS in multiple organs (Zhang et al, 2015;Fandiño et al, 2018). Therefore, we investigated the liraglutide-mediated regulation of RAS system to identify the role of the RAS in NAFLD progression and improvement.…”
Section: Liraglutide Regulates Ras Component Expression In the Liversmentioning
confidence: 99%
“…There is emerging evidence supporting an association between glucagon-like peptide-1/glucagon-like peptide-1 receptor (GLP-1/ GLP-1R) signaling and the RAS both in circulation and multiple local tissues (e.g., cardiovascular, lung, and kidney) (Zhang et al, 2015;Fandiño et al, 2018). As one of the most important incretins in the body, GLP-1 can exert hypoglycemic effects through various mechanisms, including promoting insulin secretion and islet beta cell proliferation, inhibiting apoptosis and glucagon secretion, suppressing appetite, and promoting satiety (Bifari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, transplacental administration of the GLP-1R agonist liraglutide improved the morphology of the pulmonary vascular vessel in an animal model of congenital diaphragmatic hernia in rabbits [45]. Moreover, GLP-1R activation promoted a marked induction of the ACE2 expression, which enhanced the activity of the ACE2/Ang(1-7)/MasR branch of the renin-angiotensin system, with vasodilatory instead of vasoconstrictor properties, in an animal model of FGR by perinatal food restriction of the mothers [46]. This was also observed in diabetic rats, showing right ventricle hypertrophy, which is prevented by just one-week administration of liraglutide [47].…”
Section: Glp-1mentioning
confidence: 96%
“…In vitro phosphatidylcholine secretion [43,44] In vivo SFTPs expression [42,46,47] Increase ACE2/Ang (1-7)/MasR branch of the renin-angiotensin system [46,47] Retinoic acid…”
Section: Hormone Action In Lung Development Referencesmentioning
confidence: 99%
“…et al, 2020). The integral membrane protein ACE2, which accommodates metallopeptidase domain (PD) and collectrin-like domain (CLD), controls vasoconstriction and blood pressure, and plays a vital role in antiproliferation through the maturation of angiotensinII (Ang II) to angiotensin 1-7 [Ang(1-7)], serves as an antagonist of type 1 angiotensin receptor (AT2-R) (Tikellis and Thomas, 2012;Fandiño et al, 2018). Researchers have provided dismaying evidence of T-cell infection by SARS-CoV-2.…”
Section: Mechanism Of Infection In Humanmentioning
confidence: 99%